(3CLhHI eSGFd OYhI GdCWHGA dGHf HWdGfs - (3Ydj Hf gHI Gddg Hf Ydj Hf GdMSjf, CHh GdMSf GHf CKQOj , J HYO (B507 (3g`s; (3GHf HWdGf , GdeNJGQ Hf GdMSf Hf YHOhf, CHh GdMSf,J (B458 (3g` s
(3ChdgG (B:s
(3gPg QSGdI cJHgG GdTjN GdaGVd CHh GdMSf Ydi GHf gHI Gddg LhGHkG Yf cJGH hUdg ef GdTjN CHh GdMSf jSFdg Yf CLhHg GdeSGFd GdJi VefgG GdTjN CHh GdMSf GHf HWdGf QSGdJg GdehSheg HOYhI GdCWHGA s
(3BNQgG (B:s
(3hfMf fTGgO GdehhdOjf SGYI hdGOJge bHd Cf jZJPhG HGddHf Ch HZjQg jJHQRhf TjFkG jejd Edi GdShGO ebOGQg jSjQ s
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B191 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B210s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKfi (B- (3U (B3 s
Keywords: (3GdWHs